If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln * 2x + -1ln * x + -1ln * 6 = 0 Reorder the terms for easier multiplication: 2nL * x + -1ln * x + -1ln * 6 = 0 Multiply nL * x 2nxL + -1ln * x + -1ln * 6 = 0 Multiply ln * x 2nxL + -1lnx + -1ln * 6 = 0 Reorder the terms for easier multiplication: 2nxL + -1lnx + -1 * 6ln = 0 Multiply -1 * 6 2nxL + -1lnx + -6ln = 0 Reorder the terms: -6ln + -1lnx + 2nxL = 0 Solving -6ln + -1lnx + 2nxL = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2nxL' to each side of the equation. -6ln + -1lnx + 2nxL + -2nxL = 0 + -2nxL Combine like terms: 2nxL + -2nxL = 0 -6ln + -1lnx + 0 = 0 + -2nxL -6ln + -1lnx = 0 + -2nxL Remove the zero: -6ln + -1lnx = -2nxL Combine like terms: -2nxL + 2nxL = 0 -6ln + -1lnx + 2nxL = 0 Factor out the Greatest Common Factor (GCF), 'n'. n(-6l + -1lx + 2xL) = 0Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing l to the left, all other terms to the right. Add '-1n' to each side of the equation. n + -1n = 0 + -1n Remove the zero: 0 = -1n Simplifying 0 = -1n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-6l + -1lx + 2xL)' equal to zero and attempt to solve: Simplifying -6l + -1lx + 2xL = 0 Solving -6l + -1lx + 2xL = 0 Move all terms containing l to the left, all other terms to the right. Add '-2xL' to each side of the equation. -6l + -1lx + 2xL + -2xL = 0 + -2xL Combine like terms: 2xL + -2xL = 0 -6l + -1lx + 0 = 0 + -2xL -6l + -1lx = 0 + -2xL Remove the zero: -6l + -1lx = -2xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5x-4(x+4)=2x+3 | | f(x)=3/4x^5 | | F(3)=5x+2x-7 | | 4x+9=3(x+2) | | x=221 | | m-85=11 | | n-19=47 | | 12x+7=11(x+4) | | 7x+-1(6x+7)=-2 | | 6(x+7)-6=-4(x+4) | | 91+x=137 | | 4z/-16=-8 | | 76+63=x | | 6(x+10)+4=-4(x-3)-11 | | x+6873=7000 | | x*tanx=1 | | x-2i^2+7i=yi+2xi^3 | | 7(x+7)+3=-5(X-7)-8 | | f(x)=x^3-2ax^2-37x+30a | | y+7898=8023 | | 2(5x-4)=7x+9 | | 3z/-16=8 | | 3(2x-1)+7=-(-4x-5) | | x+56=234 | | x-56=-6x | | y=490+14(-45) | | (x+1)*(x-1)-2*(x-1)=0 | | y-5(-15)=13 | | y=490+14(50) | | y=490+14(85) | | y=490+14(x) | | 5m-4m=21 |